2018
DOI: 10.1130/b31926.1
|View full text |Cite
|
Sign up to set email alerts
|

Early mammalian recovery after the end-Cretaceous mass extinction: A high-resolution view from McGuire Creek area, Montana, USA

Abstract: Changes in mammalian faunal composition and structure following the Cretaceous-Paleo gene mass extinction are central to understanding not only how terrestrial communities recovered from this ecological perturbation but also the evolution of archaic groups leading to extant mammalian clades. Here, we analyzed changes in mammalian local faunas during the earliest Paleogene biotic recovery on a small spatiotemporal scale. We compiled samples of mammals from four localities in the Hell Creek Formation and Tullock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(52 citation statements)
references
References 95 publications
1
50
1
Order By: Relevance
“…Opportunistic immigrant taxa spearheaded by archaic ungulates are common in the earliest Paleocene, possibly from refugia either to the north or south of the Western Interior (Lofgren et al, 2004;Wilson, 2014). Assemblages from the Hell Creek region of Montana indicate that recovery of mammal communities in this area took between 320 kyr to 1 myr with eutherian taxa taking 400 kyr to 1 myr to recover (Wilson, 2014;Smith et al, 2018). Lillegraven and Eberle (1999) noted that the eutherian faunas in the Ferris Formation of the Hanna Basin, the only locality currently where Pu1-3 are in direct superposition, do not show significant losses at the K-Pg but instead radiate to fill vacant niche space.…”
Section: Extinction and Recovery Across The K-pg Boundarymentioning
confidence: 98%
See 1 more Smart Citation
“…Opportunistic immigrant taxa spearheaded by archaic ungulates are common in the earliest Paleocene, possibly from refugia either to the north or south of the Western Interior (Lofgren et al, 2004;Wilson, 2014). Assemblages from the Hell Creek region of Montana indicate that recovery of mammal communities in this area took between 320 kyr to 1 myr with eutherian taxa taking 400 kyr to 1 myr to recover (Wilson, 2014;Smith et al, 2018). Lillegraven and Eberle (1999) noted that the eutherian faunas in the Ferris Formation of the Hanna Basin, the only locality currently where Pu1-3 are in direct superposition, do not show significant losses at the K-Pg but instead radiate to fill vacant niche space.…”
Section: Extinction and Recovery Across The K-pg Boundarymentioning
confidence: 98%
“…The Laramide synorgenic sediment sequence within the Denver Basin represents one of the best terrestrial records of the K-Pg boundary in the world with observed osmium and iridium anomalies, shocked quartz, extinction of flora and fauna, and a spike in abundance of fern spores that are commonly used as indicators of the boundary (Nichols and Fleming, 2002;Barclay, 2003;Raynolds and Johnson, 2003;Zaiss et al, 2014). Several important megafloral and vertebrate paleontological localities have been identified within the basin; however, the Denver Basin is relatively under-sampled in comparison to coeval sites in the San Juan Basin of New Mexico and Williston Basin of North Dakota and Montana (Archibald, 1982;Williamson, 1996;Clemens, 2002;Williamson et al, 2012;Wilson, 2013;Smith et al, 2018). There are 231…”
Section: Introductionmentioning
confidence: 99%
“…Other intervals with low CI values all fall within the plateau, and it ca n The results of this analysis are congruent with the finds from other studies. Rapid onset of recovery following the K-Pg extinction has also been observed in other analyses of Paleocene richness (Maas and Krause, 1994;Alroy, 1999Alroy, , 2000Wilson, 2013;Longrich et al, 2016), including studies that were able to incorporate the use of rarefaction to standardize for sampling (Wilson, 2014;Smith et al, 2018).…”
Section: Paleogene Recoverymentioning
confidence: 55%
“…If the Deccan traps did play a role in the weakening of late Maastrichtian terrestrial ecosystems, then there exists no evidence of these effects continuing in the aftermath of the bollide impact. Even though the majority of the volume of Deccan basalts appear to have erupted following the Chicxulub impact (Keller et al, 2016;Sprain et al, 2018), and the apparent effects of this volcanism continued to be felt in marine ecosystems into the early Paleocene (Keller et al, 2009a), major climatic deviations and terrestrial ecological downturns (Wilson, 2013(Wilson, , 2014Longrich et al, 2016;Smith et al, 2018) are unknown from the rest of the eruption period (Chenet et al, 2007;Schoene et al, 2015). The apparent drop in diversity found in this study for the To1 interval post-dates the termination of Deccan volcanism (Keller et al, 2016).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation